Tumor-Infiltrating γδ T Lymphocytes: Pathogenic Role, Clinical Significance, and Differential Programing in the Tumor Microenvironment - Lo Presti, Elena (Front Immunol, 2014)
There is increasing clinical evidence indicating that the immune system may either promote or inhibit tumor progression. Several studies have demonstrated that tumors undergoing remission are largely infiltrated by T lymphocytes [tumor-infiltrating lymphocytes (TILs)], but on the other hand, several studies have shown that tumors may be infiltrated by TILs endowed with suppressive features, suggesting that TILs are rather associated with tumor progression and unfavorable prognosis. γδ T lymphocytes are an important component of TILs that may contribute to tumor immunosurveillance, as also suggested by promising reports from several small phase-I clinical trials. Typically, γδ T lymphocytes perform effector functions involved in anti-tumor immune responses (cytotoxicity, production of IFN-γ and TNF-α, and dendritic cell maturation), but under appropriate conditions they may divert from the typical Th1-like phenotype and polarize to Th2, Th17, and Treg cells thus acquiring the capability to inhibit anti-tumor immune responses and promote tumor growth. Recent studies have shown a high frequency of γδ T lymphocytes infiltrating different types of cancer, but the nature of this association and the exact mechanisms underlying it remain uncertain and whether or not the presence of tumor-infiltrating γδ T lymphocytes is a definite prognostic factor remains controversial. In this paper, we will review studies of tumor-infiltrating γδ T lymphocytes from patients with different types of cancer, and we will discuss their clinical relevance. Moreover, we will also discuss on the complex interplay between cancer, tumor stroma, and γδ T lymphocytes as a major determinant of the final outcome of the γδ T lymphocyte response. Finally, we propose that targeting γδ T lymphocyte polarization and skewing their phenotype to adapt to the microenvironment might hold great promise for the treatment of cancer.